Beginning Google Maps Applications with PHP and Ajax - Purvis, Michael (Apress, 2012)
In the history of the Internet, 2005–2006 will be remembered as the year when online mapping finally came of age. Prior to 2005, MapQuest and other mapping services allowed you to look up directions, search for locations, and map businesses, but these searches were limited, usually to the companies the services had partnered with, so you couldn’t search for any location. On February 8, 2005, Google changed all that. As it does with many of its services, Google quietly released the beta of Google Maps to its Labs incubator (http://labs.google.com) and let word-of-mouth marketing promote the new service. By all accounts, Google Maps was an instant hit. It was the first free mapping service to provide satellite map views of any location on the earth, allowing anyone to look for familiar places. This started the “I can see my house from here” trend, and set the blogosphere abuzz with links to Google Maps locations around the world.